Recognition and Establishment of the Naulu Customary Law Community as a Customary Law Community Unit in Central Maluku Regency - Agustinus Jonas Sahetapy (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
The existence of indigenous communities in Indonesia is constitutionally recognized through Article 18B paragraph (2) of the 1945 Constitution, but legal certainty requires formal designation at the regional level. This study focuses on the process of acknowledgment and designation of the Naulu community in Central Maluku Regency as a legitimate legal entity. The aim is to highlight the importance of formal legitimacy to strengthen collective identity, customary rights, and unique governance structures of the Naulu community, which have persisted amid modernization. The research method is normative juridical, examining the alignment between national and local regulations, including Regional Regulation No. 1 of 2006. The findings show that recognition of the Naulu community is more than mere administrative formality; it is a juridical and sociological necessity to protect their sovereignty from land conflicts and cultural erosion. Establishment through Regent’s Decision or Regional Regulation is a key requirement for their acknowledgment as an independent legal entity in managing resources and adat autonomy. The main obstacles are administrative complexities and the need for in-depth verification of customary land boundaries. Enhancing formal legitimacy is believed to bolster the community’s negotiation position and support sustainable cultural preservation. Therefore, regional governments must commit to expediting this process to ensure justice for the Naulu community.